High HLA-F Expression Is a Poor Prognosis Factor in Patients with Nasopharyngeal Carcinoma - Bo Wu; Haihua Yang; Shenpeng Ying; Hongsheng Lu; Wei Wang; Jiaming Lv; Huacai Xiong; Wei Hu (Analytical Cellular Pathology)
Background and Aims. In patients with nasopharyngeal carcinoma (NPC), local treatment failure and distant metastasis contribute largely to poor outcomes. The nasopharynx is an important lymphoid tissue, and NPC tumourigenesis and development are partly attributed to immune system disorders. Human leukocyte antigen F (HLA-F) has shown a close correlation with NPC in many genome-wide association studies (GWASs). However, clinical studies rarely explore the relationship of HLA-F expression with the clinical parameters and outcomes in patients with NPC. Methods. In this study, we used immunohistochemistry to evaluate HLA-F expression in 74 paraffin-embedded NPC tissue sections and then analysed the association between HLA-F expression and clinical parameters and outcomes. The plasma concentration of soluble HLA-F (sHLA-F) in NPC patients and normal controls was also detected, via enzyme-linked immunosorbent assay (ELISA). Results. Low, moderate, and high HLA-F expression levels were observed in 47.3% (35/74), 35.1% (26/74), and 17.6% (13/74), respectively, of the tissue samples. HLA-F expression showed a significant correlation with local recurrence (p=0.037) and distant metastasis (p=0.024) and was also an independent factor for local recurrence-free survival (LRFS; p=0.016) and distant metastasis-free survival (DMFS; p=0.004). Although the mean concentration of plasma sHLA-F in the NPC patients was higher than that in the normal controls (13.63 pg/ml vs. 10.06 pg/ml), no statistical significance was observed (p=0.118). Conclusions. Our study provides the first evidence that high HLA-F expression is associated with NPC local recurrence and distant metastasis and may be regarded as a poor prognostic factor for NPC patients. Additional studies using larger sample sizes may be necessary to determine whether sHLA-F is a feasible NPC diagnostic indicator.